Transmission of 3D Scenes over Lossy Channels - Pietro Zanuttigh; Andrea Zanella; Federico Maguolo; Guido Maria Cortelazzo (International Journal of Digital Multimedia Broadcasting)
This paper introduces a novel error correction scheme for the transmission of three-dimensional scenes over unreliable networks. We propose a novel Unequal Error Protection scheme for the transmission of depth and texture information that distributes a prefixed amount of redundancy among the various elements of the scene description in order to maximize the quality of the rendered views. This target is achieved exploiting also a new model for the estimation of the impact on the rendered views of the various geometry and texture packets which takes into account their relevance in the coded bitstream and the viewpoint required by the user. Experimental results show how the proposed scheme effectively enhances the quality of the rendered images in a typical depth-image-based rendering scenario as packets are progressively decoded/recovered by the receiver.